1997
DOI: 10.1007/s004240050335
|View full text |Cite
|
Sign up to set email alerts
|

Activation of non-selective cation conductance by carbachol in freshly isolated bovine ciliary muscle cells

Abstract: In smooth muscle cells freshly isolated from the bovine ciliary body, effects of carbachol (CCh) on the membrane potential and current were examined by the whole-cell clamp method. The resting membrane potential of the muscle cells used was -60 +/- 1 mV (n = 111). Extracellular application of CCh (2 microM) depolarized the cells to -15 +/- 5 mV (n = 50) with an apparent increase in membrane conductance. Under voltage-clamp conditions, CCh (2 microM) evoked an inward current which exhibited inward-going rectifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 31 publications
6
21
0
Order By: Relevance
“…The reversal potential (Vrev) of ICCh suggested that the CChactivated non-selective cation channel is twice as permeable for Ca¥ than for Cs¤ ions (see also Takai et al 1997), similar to the value reported for the P2x-gated non-selective cation channels (Benham & Tsien, 1987;Benham, 1989;Fieber & Adams, 1991;Schneider et al 1991). When we extrapolated this result from bi-ionic 110 mÒ Ca¥-140 mÒ Cs¤ conditions to more physiological Cs¤ Tyrode solution (eqn (7)) we obtained *fCa = 0·14.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The reversal potential (Vrev) of ICCh suggested that the CChactivated non-selective cation channel is twice as permeable for Ca¥ than for Cs¤ ions (see also Takai et al 1997), similar to the value reported for the P2x-gated non-selective cation channels (Benham & Tsien, 1987;Benham, 1989;Fieber & Adams, 1991;Schneider et al 1991). When we extrapolated this result from bi-ionic 110 mÒ Ca¥-140 mÒ Cs¤ conditions to more physiological Cs¤ Tyrode solution (eqn (7)) we obtained *fCa = 0·14.…”
Section: Discussionsupporting
confidence: 54%
“…7B). The reversal potential was 19·5 ± 0·77 mV (n = 11), a value similar to the one obtained for the ACh-activated non-selective cationic current in other smooth muscle cells (Inoue & Isenberg, 1991a;Takai et al 1997). According to eqn (6), Vrev = 20 mV translates into a permeability ratio of 2:1.…”
Section: Electrophysiological Estimation Of the Ca¥ Permeability Ratiomentioning
confidence: 50%
See 1 more Smart Citation
“…The transient inward component studied in the present paper is rather unique in its selectivity for Ca 2+ , although muscarinic receptor activated cation channels permeable to Ca 2+ have been observed in other preparations (Takai et al 1997). We suggest that the cation current could play a role in maintenance of the cell's ability to contract after repeated stimulations.…”
Section: Discussionmentioning
confidence: 48%
“…The sustained component is mediated by a non-selective cation channel that does not discriminate between Ca 2+ and Na + (Lee et al 1993). Muscarinic receptor mediated cation channels that are permeable to Ca 2+ are also found in bovine ciliary muscle cells (Takai et al 1997). It is likely that both the transient and the sustained components of the inward current contribute to the contraction along with the depolarization associated with muscarinic stimulation.…”
Section: Carbachol-induced Transient Inward Currentmentioning
confidence: 99%